Si-quantum Dots (QD) and SiO2 tunnel barriers - Sutikno, Madnasri; Uda, Hashim, Prof. Dr.; Zul Azhar, Zahid Jamal, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2010)
Oxidation of Si for nanostructures on silicon-on-insulator (SOI) substrates is a key process in the fabrication of Si single electron transistor (SET). The most di cult aspect of the fabrication process is the formation of a nanometerscale island sandwiched between two small capacitors having a very thin insulator to allow electrons to pass through in a stochastic process, known as PADOX. This oxidation creates an island sandwiched between two tunnel barriers which constitutes a SET. The constriction of Si causes automatic tunnel barrier formation between source–QD and drain-QD. The unique characteristics of PADOX arises from i) the suppression of oxidation by mechanical stress, and ii) the oxidation from below.